(untitled) (Biological Sciences - PJSIR, 2003)
To maximize the yield of enzymes by Aspergillus niger nutritional and culture conditions were manipulated. The results of the study indicated that 30 –35 percent moist heat sterilized and fortified with 2-5 mg ammonium phosphate per 100 g rice bran in static cultivation, produced maximum amount of phytase in 10-17 days period.